Diagnosis of iron overload and heart disease by magnetic resonance imaging - J.C. Wood; L. Noetzli (Thalassemia Reports, 2011)
The use of Magnetic resonance imaging (MRI) to estimate tissue iron was initiated nearly three decades ago but has only become a practical reality in the last ten years. MRI is most often used to estimate hepatic and cardiac iron in patients with thalassemia or sickle cell disease and has largely replaced liver biopsy for liver iron quantification. The ability of MRI to image extra hepatic organs has really transformed our understanding of iron mediated toxicity in transfusional siderosis. For decades, iron cardiomyopathy was the leading cause of death in thalassemia major, but it is now relatively rare in centers with regular MRI screening. Early recognition of cardiac iron loading allows more gentle modifications of iron chelation therapy prior to life threatening organ dysfunction. Serial MRI evaluations have demonstrated differential kinetics of uptake and clearance among the difference organs of the body. Although elevated serum ferritin and liver iron concentration increase the risk of cardiac and endocrine toxicities, extra hepatic iron deposition and toxicity occurs in many patients despite having low total body iron stores; there is no safe liver iron level in chronically transfused patients. Instead, the type, dose, and pattern of iron chelation therapy all contribute to whether cardiac iron accumulation will occur. These observations, coupled with the advent of increasing options for iron chelation therapy, are allowing clinicians to more appropriately tailor chelation therapy to individual patient needs, producing greater efficacy with fewer toxicities. With the decline in cardiac mortality, future frontiers in MRI monitoring including better prevention of endocrine toxicities, particularly hypogonadotropic hypogonadism and diabetes. These organs also serve as early warning signals for inadequate control of non-transferrin bound iron, a risk factor for cardiac iron loading. Thus MRI assessment of extra hepatic iron stores is a critical monitoring tool for chronically transfused patients. Further prospective work is necessary to determine whether markers of endocrine and exocrine pancreatic function can be used as surrogates of cardiac risk in regions where MRI is not available.   核磁共振成像(MRI)在大约30年前就开始用于估算组织铁，但仅在最近10年内，才达到实用目的。 MRI最常用于估算地中海贫血或镰状细胞病患者的肝脏铁含量和心脏铁含量，并在很大程度上取代了量化肝铁组织的肝脏活体组织检查。 MRI的肝外器官成像功能让我们重新理解了输血性铁质沉着症的铁介导毒性。 几十年来，缺铁性心脏病是地中海贫血患者死亡的主要原因，但是在定期进行MRI筛查的卫生中心很少发生这样的情况。 如果心脏铁负载能较早确诊，医生就可适当修改铁螯合疗法，避免发生威胁生命的器官功能障碍。 MRI系列评估表明，身体中不同的器官有不同的吸收动力和清除动力。 血清铁蛋白和肝铁浓度的上升会增加心脏毒性和内分泌毒性的风险，即使患者体内的铁存储量很低，仍然有很多患者发生肝外铁沉积和铁毒；慢性输血病人体内没有“安全”的肝铁浓度。 反而，铁螯合疗法的类型、剂量和模式都会加大心脏铁沉积的发生几率。 通过这些观察并结合越来越多的铁螯合疗法，临床人员可以根据每个病人的需要，制定更适当的螯合疗法，产生更显著的疗效，同时毒性更少。 随着心脏病死亡率的降低，未来MRI监测的新领域包括更好地预防内分泌毒性，尤其是低促性腺素性功能减退症和糖尿病。 这些器官也可作为早期的警告信号，暗示非转铁蛋白结合铁控制的不足。非转铁蛋白结合铁是心脏铁负载的一个危险因素。 因此，肝外铁存储量的MRI评估是慢性输血病人的关键监测工具。 将来有必要在没有MRI的地区展开进一步工作，确定内分泌和外分泌胰腺功能的标记器是否可以排出心脏风险。